IMPLEMENTATION OF CUSTOMER PERCEIVED VALUE AS A MARKETING STRATEGY FOR STREAMING SERVICES IN COMPETING WITH CINEMAS FOR MOVIE CONSUMPTION (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The rapid advancement of digital technology has transformed entertainment consumption, encouraging consumers to shift from traditional cinemas to paid streaming services. This study aims to explore how consumers in Tangerang City perceive the Customer Perceived Value (CPV) of paid streaming services, identify the CPV dimensions influencing consumer preferences, and examine the role of CPV as a competitive marketing strategy against cinemas. A qualitative approach was employed using semi-structured interviews, observations, and document analysis involving paid streaming service users aged 18–35 years in Tangerang City. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by NVivo 12 for coding and thematic analysis. The findings indicate that CPV is perceived as a multidimensional construct comprising functional, emotional, social, and price value. Functional value, reflected in convenience, flexibility, accessibility, and content variety, together with price value through affordability and cost efficiency, emerged as the strongest determinants of consumer preference. While paid streaming services have become the preferred option for everyday entertainment due to their practicality and flexibility, cinemas remain relevant by offering immersive audiovisual experiences and unique social interactions. These findings suggest that streaming services partially substitute rather than completely replace cinemas. Overall, the implementation of CPV strengthens the competitive position of paid streaming services by aligning value creation with evolving consumer entertainment preferences.